Has the new bail-in framework increased the yield spread between subordinated and senior bonds? - Irene Pablos Nuevo (European Central Bank (ECB), 2019)
This paper investigates the impact of the introduction and implementation of the new EU bail-in framework on the banks subordinated bond yield spreads over senior unsecured bonds, and links the bond yields developments with the characteristics of the issuing entities and the economic and financial environment. The analysis does not show evidence of a significant and generalized increase in the spreads as a result of a higher risk perception in the sample under review. The results reinforce the relevance of the Tier 1 capital ratio for making subordinated debt safer, while markets price the higher risk of banks with less stable sources of funding in their liability/capital structures. Market conditions and economic environment variables also play a key role in explaining bond spreads. Interestingly, after the introduction of the new bail-in framework, there is a convergence between the bond yields of the GSIBs and the non-GSIBs, which could point out to a reduction in the market perception of the so called "too big to fail" public implicit guarantee. Nonetheless, this convergence is mostly driven by the reduction of the yields of bonds issued by banks not categorized as GSIBs, and not by significant increases in the GSIBs' bond yields.
Keywords: G12; G14; G28; 330; Bank bond yields; bail-in; too big to fail